Comparative analysis of spermatids of Rhipicephalus sanguineus sensu lato (Ixodidae) and Ornithodoros rostratus ticks (Argasidae): morphophysiology aimed at systematics - Sampieri, Bruno Rodrigues [UNESP]; Calligaris, Izabela Bragião [UNESP]; Silva Matos, Renata da[UNESP]; Páez, Fredy Arvey Rivera [UNESP]; Bueno, Odair Corrêa [UNESP]; Camargo-Mathias, Maria Izabel [UNESP] (Springer, 2015)
The phylogenetic relationships among tick species (Acari: Ixodida) have been revisited by several researchers over the last decades. Two subfamilies, Rhipicephalinae (Ixodidae) and Ornithodorinae (Argasidae), deserve special attention. The male reproductive system morphology, as well as the ultrastructure of the germ cells, may provide important information for phylogeny and systematics of metazoan groups, with spermatozoa exhibiting characters that can be used for this purpose. With that information in mind, this study aimed at evaluating, through a comparative analysis, the morphology of the male reproductive systems and germ cells of ticks species Rhipicephalus sanguineus and Ornithodoros rostratus. In order to do that, histology and scanning electron microscopy techniques were used. The results have shown that despite the similarities in the general morphology of the male reproductive system among studied Ixodida so far, there are morphological differences among the species studied herein, mainly the U-shaped testis (ancestral character) in O. rostratus and the pair testes (derived character) in R. sanguineus, and the general morphology of germ cells (spermatids V). Besides that, the morphological changes observed during the spermiogenesis appear to be different between the species studied here, probably characterizing the two families considered. The data generated in this study showed the importance of comparative internal morphology studies, mainly in regard to spermatology, despite the morphological data obtained herein not being enough to product a cladogram (sperm cladistics), it was already possible to observe clear differences among families Argasidae and Ixodidae in regard to the organization of their male reproductive systems and concerning the external morphology of spermatids. Data yet to be obtained through transmission electron microscopy techniques will allow the application of spermiocladistics and spermiotaxonomy as tools for tick systematics.
Keywords: Comparative histology; Sperm taxonomy; Testes; Ticks